A combined experimental and DFT investigation of disazo dye having pyrazole skeleton - Şener, Nesrin; Bayrakdar, Alpaslan; Kart, Hasan Hüseyin; Şener, İzzet (Elsevier BV, 2017)
Abstract Disazo dye containing pyrazole skeleton has been synthesized. The structure of the dye has been confirmed by using FT-IR, 1 H NMR, 13 C NMR, HRMS spectral technique and elemental analysis. The molecular geometry and infrared spectrum are also calculated by the Density Functional Theory (DFT) employing B3LYP level with 6-311G (d,p) basis set. The chemical shifts calculation for 1 H NMR of the title molecule is done by using by Gauge-Invariant Atomic Orbital (GIAO) method by utilizing the same basis sets. The total density of state, the partial density of state and the overlap population density of state diagram analysis are done via Gauss Sum 3.0 program. Frontier molecular orbitals such as highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) and molecular electrostatic potential surface on the title molecule are predicted for various intramolecular interactions that are responsible for the stabilization of the molecule. The experimental results and theoretical values have been compared.
Keywords: Highest occupied molecular orbital; Musculoskeletal system; Frontier molecular orbitals; Lowest unoccupied molecular orbital; Chemical bonds; Azo dyes; Intramolecular interactions; Disazo dyes; Molecules; DFT; Population statistics; Dis-azo dyes; Orbital calculations; Solvatochromism; Diazo-coupling reaction; Diazo couplings; Molecular orbitals; Density functional theory; Molecular electrostatic potentials; Solvatochromisms; Quantum chemistry; 3. Good health